Effects of diacerein on cartilage and subchondral bone in early stages of osteoarthritis in a rabbit model - Permuy, María (BMC Vet Res, 2015)
BACKGROUND: Osteoarthritis is thought to be the most prevalent chronic and disabling joint disease in animals and humans. At present, there is no ideal treatment option. The aim of this study was to assess the effects of the treatment with oral diacerein on articular cartilage, synovial membrane and subchondral bone in an experimental rabbit model of osteoarthritis by micro-CT evaluation and histological analysis. To this purpose, osteoarthritis was surgically induced on one knee of 16 rabbits using the contralateral knee as healthy controls. Treatment was started three weeks later and lasted eight weeks. Animals were divided into two groups for treatment: Placebo (treated daily with oral saline) and diacerein (treated orally with 1.5 mg/kg/day of diacerein). RESULTS: Sample analysis revealed that this model induced osteoarthritis in the operated knee joint. Osteoarthritis placebo group showed a significant increase in non-calcified cartilage thickness and volume with respect to the control placebo group and important changes in the synovial membrane; whereas the parameters measured in subchondral bone remained unchanged. In the osteoarthritis diacerein-treated group the results showed an improvement with respect to the OA placebo group in all parameters, although the results were not statistically significant. CONCLUSION: The results of this animal study suggested that the diacerein treatment for OA may be able to ameliorate the swelling and surface alterations of the cartilage and exert an anti-inflammatory effect on the synovial membrane, which might contribute to OA improvement, as well as an anabolic effect on subchondral trabecular bone.